Factors Related to the Performance of Cadres in the Implementation of Community Based Health Service Activities - Rahmayanti, Widi; Yogaswara, Dadan; Fitriani, Sinta; Hidayani , Wuri Ratna; Tagum, Kenny Nino H.; Turiano, Lorraine (The Indonesian Institute of Science and Technology Research, 2022)
Posyandu is a Community-based health service managed and organized by the Community. It is responsible for implementing health development to empower the community and provide convenience in obtaining essential health services to accelerate the reduction of maternal and infant mortality. This study aims to determine what factors are related to the role of cadre performance in implementing Posyandu activities. This research method is an analytic description using a literature review design. The results showed no relationship between knowledge factors, age, incentives, training, education, attitudes, and motivation towards cadre performance, and there was no relationship between husband support and cadre performance.